CONSOLIDATED DECISION-MAKING: THE CANADIAN EXPERIENCE - VanKessel, Gerry (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2001)
As part to the 1951 Convention and its 1967 Protocol, Canada is obliged to protect persons on its territory who have a well founded fear of persecution based on their nationality, membership in a social group, or political opinion. Inspite of the fact that the Convention refugee definition has been fully incorporated into the Immigration Act, the process of determining refugee status and protection needs in Canada has been criticized by various organizations including the Auditor General of Canada and the Legislative Review Advisory Group. The recommendations made by the Auditor General include that Citizenship and Immigration should ensure that the risk of return review is within the scope of the objectives set out for the Post-Determination Refugee Class and that it is carried out in an efficient and timely manner. The Legislative Review Advisory Group found that not only the current system was complex, but also that some of Canada’s international commitments have not been fully incorporated into domestic legislation. It was determined that the Immigration and Refugee Board would become responsible for applying all protection criteria in a consolidated protection definition, and, hence, would be the expert body to administer this definition. A single process in which all the facts are before the same decision-maker will promote fairness, consistency and efficiency.